A fine mapping of single nucleotide variants and haplotype analysis of IL13 gene in patients with Leishmania guyanensis-cutaneous leishmaniasis and plasma cytokines IL-4, IL-5, and IL-13 - Junior, José do Espírito Santo; Souza, Josué Lacerda de; Silva, Lener Santos da; Silva, Cilana Chagas da; Nascimento, Tuanny Arruda do; Souza, Mara Lúcia Gomes de; Cunha, Alyne Farias da; Batista, Jacqueline da Silva; Neto, José Pereira de Moura; Guerra, Marcus Vinitius de Farias; Ramasawmy, Rajendranath (Frontiers in Immunology, 2023)
Leishmaniasis continues to pose a substantial health burden in 97 countries worldwide. The progression and outcome of Leishmania-infection are influenced by various factors, including the cytokine milieu, the skin microbiota at the infection site, the specific Leishmania-species involved, the genetic background of the host, and the parasite load. In endemic regions to leishmaniasis, only a fraction of individuals infected actually develops the disease. Overexpression of IL-13 in naturally resistant C57BL/6 mice renders them susceptible to L. major-infection. Haplotypes constructed from several single nucleotide variant (SNV) along a chromosome fragment may provide insight into any SNV near the fragment that may be genuinely associated with a phenotype in genetic association studies. We investigated nine SNVs (SNV1rs1881457A>C, SNV2rs1295687C>G, SNV3rs2069744C>T, SNV4rs2069747C>T, SNV5rs20541A>G, SNV6rs1295685A>G, SNV7rs848A>C, SNV8rs2069750G >C and SNV9rs847T>C) spanning the entire IL13 gene in patients with L. guyanensis cutaneous leishmaniasis (Lg-CL). Our analysis did not reveal any significant association between the SNVs and susceptibility/protection against Lg-CL development. However, haplotype analysis, excluding SNV4rs2069747 and SNV8rs2069750 due to low minor allele frequency, revealed that carriers of the haplotype-CCCTAAC had a 93% reduced likelihood developing Lg-CL. Similarly, the haplotypes ACCCGCT (ORadj=0.02 [95% CI 0.00 – 0.07]; p-value 6.0x10-19) and AGCTAAC (ORadj=0.00[95% CI 0.00–0.00]; p-value 2.7x10-12) appeared to provide protection against the development of Lg-CL. Conversely, carriers of haplotype-ACCTGCC have 190% increased likelihood of developing Lg-CL (ORadj=2.9 [95%CI 1.68–5.2]; p-value 2.5x10-6). Similarly, haplotype-ACCCAAT (ORadj=2.7 [95%CI 1.5–4.7]; p-value 3.2 x10-5) and haplotype-AGCCGCC are associated with susceptibility to the development of Lg-CL (ORadj=1.7[95%CI 1.04–2.8]; p-value 0.01). In our investigation, we also found correlation between the genotypes of rs2069744, rs20541, rs1295685, rs847 and rs848 and plasma IL-5 levels among Lg-Cl patients. Furthermore, rs20541 showed a correlation with plasma IL-13 levels among Lg-Cl patients, while rs2069744 and rs848 showed a correlation with plasma IL-4 levels among the same group. Overall, our study identifies three haplotypes of IL13 associated with resistance to disease development and three haplotypes linked to susceptibility. These findings suggest the possibility of a variant outside the gene region that may contribute, in conjunction with other genes, to differences in susceptibility and partially to the pathology.